REFLECHIR SUR LES TICE EN CLASSE D’ANGLAIS: CAS DES ENSEIGNANTS EN FORMATION INITIALE - Kotuła, Krzysztof (Neofilolog, 2019)
The goal of the present paper is to question the validity of the claim which sees reflection as an important part of the work of an efficient language teacher. A quasi-experiment was conducted by the author in order to determine whether reflection is a factor which can in some way influence the teacher’s capacity to plan a FL lesson effectively, incorporating new technologies. A reflective thinking questionnaire (RTQ, Kember et al., 2000) was administered to assess the level of reflective thinking in 47 university students. Next, their lesson projects were evaluated by two independent experts. The correlational study seems to show that reflection may indeed be a factor which influences the quality of the work of a foreign language teacher in an important way.